APPLICATION OF EXECUTION OF FIDUCIARY GUARANTEE OBJECTS IN FINANCE COMPANIES AFTER THE CONSTITUTIONAL COURT DECISION NUMBER 18 / PUU-XVII / 2019 IN THE JURISDICTIONAL AREA SERANG DISTRICT COURT - Lukman Hakim; Faridatul Fauziyah; Rani Sri Agustina (JHR (Jurnal Hukum Replik), 2022)
This article aims to find out the Implementation of the Execution of the Object of Fiduciary Guarantees after the Decision of the Constitutional Court Number 18/PUU-XVII/2019 in the Jurisdiction Area of the Serang City District Court. This study elaborates on two objects to determine the execution of fiduciary guarantees after the Constitutional Court Decision Number 18/PUU-XVII/2019 in the jurisdiction of the Serang District Court. This study uses a descriptive qualitative research method approach through in-depth interviews. The results of the study stated that the financing company carried out the execution of the object of the fiduciary guarantee based on the procedures, mechanisms and provisions according to their respective internals. This means that creditors are always guided by the Standard Operating Procedures. In addition, after the Constitutional Court Decision No. 18/PUU-XVII/2019 there are no changes in executing the object of fiduciary guarantee. Finance companies are reluctant to apply for execution through the courts because of bureaucratic problems. So that the use of collection service companies is still applied by a number of finance companies in the jurisdiction of the Serang District Court.